Induction of Mucosal IgA–Mediated Protective Immunity Against Nontypeable Haemophilus influenzae Infection by a Cationic Nanogel–Based P6 Nasal Vaccine - Nakahashi-Ouchida, Rika; Mori, Hiromi; Yuki, Yoshikazu; Umemoto, Shingo; Hirano, Takashi; Uchida, Yohei; Machita, Tomonori; Yamanoue, Tomoyuki; Sawada, Shin-ichi; Suzuki, Masashi; Fujihashi, Kohtaro; Akiyoshi, Kazunari; et al. (Frontiers in Immunology, 2022)
Nontypeable Haemophilus influenzae (NTHi) form a major group of pathogenic bacteria that infect the nasopharynx and cause otitis media in young children. At present, there is no licensed vaccine for NTHi. Because NTHi colonizes the upper respiratory tract and form biofilms that cause subsequent infectious events, a nasal vaccine that inducing NTHi-specific secretory IgA capable of blocking the biofilm in the respiratory tract is thus desirable. Here, we developed a cationic cholesteryl pullulan–based (cCHP nanogel) nasal vaccine containing the universal NTHi surface antigen P6 (cCHP-P6). Nasal immunization of mice with cCHP-P6 effectively induced P6-specific IgA in mucosal fluids. The vaccine-induced P6-specific IgA showed direct binding to the NTHi via the surface P6 proteins, resulting in the inhibition of NTHi biofilm formation. cCHP-P6 nasal vaccine thus protected mice from an intranasal NTHi challenge by reducing NTHi colonization of nasal tissues, eventually eliminated the bacteria. The vaccine-induced IgA also bound to different NTHi clinical isolates from patients with otitis media and inhibited these NTHi attachment to a three-dimensional in vitro model of the human nasal epithelial surface. Therefore, the cCHP-P6 nanogel nasal vaccine induced effective protection in the airway mucosa, making it a strong vaccine candidate to prevent infectious diseases caused by NTHi.